2019
DOI: 10.1038/s41598-019-40787-0
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Transcriptome and Methylome Analysis in Human Skeletal Muscle Anabolism, Hypertrophy and Epigenetic Memory

Abstract: Transcriptome wide changes in human skeletal muscle after acute (anabolic) and chronic resistance exercise (RE) induced hypertrophy have been extensively determined in the literature. We have also recently undertaken DNA methylome analysis (850,000 + CpG sites) in human skeletal muscle after acute and chronic RE, detraining and retraining, where we identified an association between DNA methylation and epigenetic memory of exercise induced skeletal muscle hypertrophy. However, it is currently unknown as to whet… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
159
1
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 100 publications
(174 citation statements)
references
References 73 publications
12
159
1
2
Order By: Relevance
“…Yet, in comparing our results to the current literature, we identified no studies that examined a combined lifestyle intervention among healthy adults with DNA methylation pathway analysis. However, a recent study by Turner et al examined the impact of chronic versus acute resistance exercise on DNA methylation pathways in the skeletal muscle [55]. Even though this study only used the KEGG pathway database, the results identified several significant pathways related to cancer including those related to proteoglycans, transcriptional regulation, colorectal cancer, and small cell lung cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Yet, in comparing our results to the current literature, we identified no studies that examined a combined lifestyle intervention among healthy adults with DNA methylation pathway analysis. However, a recent study by Turner et al examined the impact of chronic versus acute resistance exercise on DNA methylation pathways in the skeletal muscle [55]. Even though this study only used the KEGG pathway database, the results identified several significant pathways related to cancer including those related to proteoglycans, transcriptional regulation, colorectal cancer, and small cell lung cancer.…”
Section: Discussionmentioning
confidence: 99%
“…; Turner et al . ). Ethical approval was granted by the NHS West Midlands Black Country, UK, Research Ethics Committee (NREC approval no.…”
Section: Methodsmentioning
confidence: 97%
“…Recently, it has been reported that DNA methylation is also affected by RE in human skeletal muscles [8,9]. Seaborne et al [8] reported that the frequency of genome-wide hypomethylation at the CpG sites in human skeletal muscle was increased after chronic RE training (9,153 sites), maintained during the detraining period (8,891 sites), and further enhanced in response to reloading (18,816 sites).…”
Section: Plos Onementioning
confidence: 99%
“…Seaborne et al [8] reported that the frequency of genome-wide hypomethylation at the CpG sites in human skeletal muscle was increased after chronic RE training (9,153 sites), maintained during the detraining period (8,891 sites), and further enhanced in response to reloading (18,816 sites). Turner et al [9] further reported that the expression of 592 of 5,262 genes that were hypomethylated at their CpG sites after chronic RE training was up-regulated. These results indicate that RE training altered the status of genes activation, in agreement with our present results which show an enhancement of the hallmarks of active transcription in histone distributions after RE training.…”
Section: Plos Onementioning
confidence: 99%
See 1 more Smart Citation